2013
DOI: 10.1007/s00300-013-1366-9
|View full text |Cite
|
Sign up to set email alerts
|

Distribution patterns of polychaete fauna in an Arctic fjord (Hornsund, Spitsbergen)

Abstract: Polychaetes are one of the most important groups of benthic organisms in marine ecosystems. They dominate on the Arctic shelf and play an important role in ecosystem functioning. This study focuses on the polychaete biodiversity and their distribution patterns in Hornsund, an open glacial fjord, in western Spitsbergen and provides important baseline data for future studies of temporal fluctuations in benthic fauna. The main aim of this study was to assess how the polychaete abundance, biomass, diversity, commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 58 publications
4
6
0
Order By: Relevance
“…Studies of polychaete diversity in Ezcurra Inlet and in Admiralty Bay as a whole showed high number of polychaete assemblages associated with different microhabitats (Siciński, 2004;Pabis & Siciński, 2010), while in Kongsfjorden the character of bottom deposits was less diversified resulting in more simple assemblage differentiation into three main faunal groupings associated with the inner, middle and outer areas of this inlet (Włodarska-Kowalczuk & Pearson, 2004). A similar pattern was also observed in Hornsund (Kędra et al, 2013). Our small scale study was focused on two clearly defined similar habitats to allow for more reliable comparisons.…”
Section: Discussionsupporting
confidence: 60%
“…Studies of polychaete diversity in Ezcurra Inlet and in Admiralty Bay as a whole showed high number of polychaete assemblages associated with different microhabitats (Siciński, 2004;Pabis & Siciński, 2010), while in Kongsfjorden the character of bottom deposits was less diversified resulting in more simple assemblage differentiation into three main faunal groupings associated with the inner, middle and outer areas of this inlet (Włodarska-Kowalczuk & Pearson, 2004). A similar pattern was also observed in Hornsund (Kędra et al, 2013). Our small scale study was focused on two clearly defined similar habitats to allow for more reliable comparisons.…”
Section: Discussionsupporting
confidence: 60%
“…The number of sampling points was high, although the samples were not distributed on a regular grid, as is recommended for species distribution modelling (Drewnik et al 2016b). However, the set of species collected in the present study seems to be very complete, considering the obtained species accumulation curve (a similar result was obtained for other taxa collected in our projects; e.g., Kędra et al 2013). We found four new species for the area, including a single specimen of Acantotrochus mirabilis, which is a deep-water holothurian that has also been reported from Norwegian and Greenland seas below depths of 1000 m (Gebruk et al 2014), but our record is a distinctly shallow one (250 m Brought to you by | MIT Libraries Authenticated Download Date | 5/10/18 2:20 PM all of wide boreal or circumpolar distributions, are known from Norway but had not been recorded so far north.…”
Section: Discussionsupporting
confidence: 56%
“…The much lower abundance and diversity of the isopod fauna in the Ezcurra Inlet, compared to the central basin of the Admiralty Bay, can be quite easily explained by the differences in the hydrological and sedimentary regimes (Pecherzewski 1980;Szafranski and Lipski 1982;Rudowski and Marsz 1996;Siciński 2004;Campos et al 2013). Glacial fjord fauna is generally impoverished in terms of biodiversity and abundance on account of various types of disturbance, such as increased mineral sedimentation and silting of bottom deposits (Włodarska-Kowalczuk and Pearson 2004;Siciński et al 2011;Kędra et al 2013). Generally, a gradual increase in macrofaunal abundance and diversity is observed along the polar fjord axis, and is accompanied by changes in species composition (Siciński 2004;Włodarska-Kowalczuk and Pearson 2004;Kedra et al 2013).…”
Section: Discussionmentioning
confidence: 99%